Spectacular sports records - Kallen, Stuart A., 1955-; Wallner, Rosemary, 1964- (Edina, Minn. : Abdo & Daughters ; Minneapolis, Minn. : Distributed by Rockbottom Books, 1991)
Presents world records in the field of sports, including the fastest sport, the longest bike race, and the batter with the most homeruns.
Keywords: Sports records -- Juvenile literature; Sports records; World records